2008
DOI: 10.1203/pdr.0b013e318163a897
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Intracellular T-Helper 1 Interferon-Gamma in Blood of Newly Diagnosed Children With Crohn's Disease and Age-Related Changes in Th1/Th2 Cytokine Profiles

Abstract: ABSTRACT:Abnormal cytokine production by T-helper 1 (Th1)/ T-helper 2 (Th2) lymphocytes has been implicated in the pathogenesis of inflammatory bowel disease (IBD). Few studies have examined Th1/Th2 cytokine status in pediatric IBD patients, and results have been inconsistent. We used flow cytometric detection of intracellular IFN-␥/IL-4 cytokine production to investigate CD4 ϩ , Th1, and Th2 cells in the peripheral blood of children with untreated, newly diagnosed Crohn's disease (CD) (n ϭ 23) and matched hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
4
14
4
Order By: Relevance
“…This supports our previous observation as well as other published data in treatment-naïve pediatric CD patients. 24, 26 These results, however, are in contrast to findings from other studies that have evaluated the Th1/Th2 profiles in the intestinal mucosa and/or peripheral blood associated with CD. In adults, increased expression of IFN-γ was found in peripheral blood or intestinal tissue of adult CD patients compared with controls, in line with the accepted dogma of a Th1-mediated mechanism of disease.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…This supports our previous observation as well as other published data in treatment-naïve pediatric CD patients. 24, 26 These results, however, are in contrast to findings from other studies that have evaluated the Th1/Th2 profiles in the intestinal mucosa and/or peripheral blood associated with CD. In adults, increased expression of IFN-γ was found in peripheral blood or intestinal tissue of adult CD patients compared with controls, in line with the accepted dogma of a Th1-mediated mechanism of disease.…”
Section: Discussioncontrasting
confidence: 94%
“…In our previous study, newly diagnosed pediatric CD patients also possessed lower IFN-γ compared with healthy controls but the IL-4 did not differ significantly between the two groups. 24 In the present study, IL-6 percentages did not differ between the two pediatric groups. No differences in IFN-γ, IL-4, and IL-6 percentages were found between adult CD patients and controls.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…Newborn children have a low production of IFN-c and an increase in IFN-c production is thought to be related to the maturation of the immune system [32]. Studies have found a decrease in intracellular levels of cytokines or a decline in T and B cells with age [33,34]. The shift from Th2 to Th1 is not supported by an increase of IFNc with age in this study.…”
Section: Changes With Agecontrasting
confidence: 76%
“…T-helper cells are a subgroup of lymphocytes that activate and direct other immune cells through release of cytokines. An imbalance between Th1 and Th2 cytokines has been implicated in the pathogenesis of IBD, particularly CD (Holland et al, 2008). Moreover, an increase in proinflammatory cytokines, mainly Th1 cytokines, is observed in patients with CD, also suggesting that CD is a Th1-mediated disease (Neurath et al, 1997).…”
Section: Discussionmentioning
confidence: 99%